Deep-Learning-Based Method for the Identification of Typical Crops Using Dual-Polarimetric Synthetic Aperture Radar and High-Resolution Optical Images - Xiaoshuang Ma; Le Li; Yinglei Wu (Remote Sensing)
Timely monitoring of distribution and growth state of crops is crucial for agricultural management. Remote sensing (RS) techniques provide an effective tool to monitor crops. This study proposes a novel approach for the identification of typical crops, including rapeseed and wheat, using multisource remote sensing data and deep learning technology. By adopting an improved DeepLabV3+ network architecture that integrates a feature-enhanced module and an attention module, multiple features from both optical data and synthetic aperture radar (SAR) data are fully mined to take into account the spectral reflectance traits and polarimetric scattering straits of crops. The proposal can effectively address the limitations of using a single data source, alleviating the misclassification problem brought by the spectral similarity of crops in certain bands. Experimental results demonstrate that the proposed crop identification DeepLabV3+ (CI-DeepLabV3+) method outperforms traditional classification methods and the original DeepLabV3+ network, with an overall accuracy and F1 score of 94.54% and 94.55%, respectively. Experimental results also support the conclusion that using multiple features from multi-source data can indeed improve the performance of the network.